COMMUNITY SERVICE TEACHERS’ COMPETENCY IMPROVEMENT IN SAMOSIR DISTRICT TOWARDS TOURISM CITY - Mailani, Elvi; Heniwaty, Yusnizar; Zati, Vidya Dwi Amalia (Universitas Negeri Medan, 2018)
AbstractPartners who are the target of community service program are teachers in Samosir District area. Samosir was chosen because the position of the region was on the shores of Lake Toba, and according to the vision and mission of the Samosir District government, Samosir will become a tourism city. Teacher competencies and abilities must also be improved in order to be able to support the mission and vision. Based on observations and interviews there are 2 main problems faced by partners, includes: (1) pedagogical competencies, (2) professional competencies. Based on these problems, several solutions were offered, including: workshop and mentoring activities. Specific targets and outputs that will be generated in community service program includes: (1) learning program plan (2) book of questions bank, (3) book and CD of songs and dance collections in Batak area, (4) Guidance book on 2013 curriculum, (5) model teacher of English language, Nntural sciences and mathematics lessons. The implementation of community service program to improve teacher competency in Samosir District will be carried out in a gradual, sustainable and comprehensive manner. This process is carried out through workshop and mentoring methods to provide provision and improvement of competencies for teachers which can later be implemented in the learning process in the classroom as an effort to improve students' abilities in realizing the vision and mission of Samosir Regency towards a tourism city.Keywords: Teachers’ Competency Accompaniment.